1981
DOI: 10.1042/bst0090489
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans: Their structure, interactions and molecular organization in cartilage

Abstract: The term 'proteoglycan' was introduced in 1967 (see Balazs. 1970) to describe the family of molecules in which glycosaminoglycan chains are linked to protein. However. their rate of diffusion into textbooks of biochemistry has been rather slow, and I will therefore begin this presentation with a general introduction, which I hope will set the basis for their structural identity and indicate how their properties may be of importance in a broad biological context, before describing in more detail studies with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
8

Year Published

1985
1985
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 11 publications
(13 reference statements)
2
57
0
8
Order By: Relevance
“…A typical feature of hyaline cartilage is the formation of high molecular weight proteoglycan aggregates (31). These were observed in primary monolayer cultures (Figure 2) and in first passage on freshly isolated, "native" chondrocytes and cultured chondrocytes (CC), and these were compared with cultured fibroblasts (CF) of foreskin or synovial tissue origin.…”
Section: Resultsmentioning
confidence: 99%
“…A typical feature of hyaline cartilage is the formation of high molecular weight proteoglycan aggregates (31). These were observed in primary monolayer cultures (Figure 2) and in first passage on freshly isolated, "native" chondrocytes and cultured chondrocytes (CC), and these were compared with cultured fibroblasts (CF) of foreskin or synovial tissue origin.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it seems likely that HA 10 is the minimum length of HA able to occupy the HA-binding site on G1, but that HA 12 has slightly tighter binding. Earlier estimates of the footprint of aggrecan on HA suggested that at maximal packing density it occupied a longer stretch of HA (ϳHA 18 ) than was part of the minimal binding site (31) and more recent experiments comparing the binding of recombinant G1 to HA 32 and HA 40 also suggested a longer site occupied, which may result from negative cooperativity (13). Alternatively, this may be caused by the spatial constraints of how close G1 domains (which each have 2 Link modules and an Ig fold) can pack when bound to HA.…”
Section: Effect Of Ph On the Binding Of The G1 Domain Of Aggrecan Withmentioning
confidence: 99%
“…In these aggregates proteoglycan monomers interact with link protein and each of these molecules interacts with hyaluronic acid (1). As many as 100 proteoglycan monomers and link proteins can interact with a single hyaluronic acid polymer (2). The domains within link protein that allow for these characteristic molecular associations can begin to be identified from the analysis of the amino acid sequence and its gene structure.…”
mentioning
confidence: 99%